Motherless Brooklyn [videorecording (DVD)] - Norton, Edward; Willis, Bruce, 1955-; Roberts, Dallas; Baldwin, Alec, 1958- (Warner Home Video, 2020)
Lionel Essrog is a lonely private detective afflicted with Tourette's Syndrome. He ventures through 1950s New York trying to solve his friend's murder. Armed only with a few clues and the powerful engine of his obsessive mind, Lionel unravels closely guarded secrets that hold the fate of the whole city in the balance.